A review of RUNX2 genetic interactions and their role in cardiovascular disease - Christine, Anastasia; Rohman, Mohammad Saifur; Yogibuana, Valerinna (Universitas Brawijaya, 2026)
Cardiovascular diseases (CVD) remain the leading cause of global mortality, with underlying factors such as genetics, environment, and lifestyle interacting in complex and multiple ways. Runt-related transcription factor 2 (RUNX2), traditionally associated with osteogenesis, has gained recognition for its critical role in cardiovascular health. RUNX2 contributes to vascular calcification (VC), endothelial dysfunction, and myocardial fibrosis, thereby accelerating CVD progression. Its expression is influenced by multiple upstream regulators relevant to vascular pathology, such as BMP2/SMAD, Wnt/β-catenin, and ERK signaling, along with epigenetic mechanisms and gene-environment interactions such as oxidative stress, hyperglycemia, and dyslipidemia. Genetic variants in RUNX2 and environmental variables including diet and physical inactivity, amplify its activation, worsening VC and cardiovascular risk. RUNX2 reduces endothelial nitric oxide bioavailability, enhances vascular inflammation, and activates profibrotic signaling in cardiac tissue, promoting vascular dysfunction and myocardial remodeling. Circulating RUNX2 levels and genetic variations exhibit potential as diagnostic and predictive indicators for cardiovascular disease. Severalpharmaceutical agents including metformin, empagliflozin, and statins, as well as natural substances such green tea polyphenols and green coffee extract, have demonstrated partial modulatory effects on RUNX2 activity. Moreover, genome-editing tools such as CRISPR-Cas9 present future opportunities for selective RUNX2 targeting. Comprehensive understanding of RUNX2 regulation and its interaction with genetic and environmental factors offers novel opportunities for personalized CVD prevention and treatment approaches through lifestyle modification, pharmacotherapy, and gene-based interventions in the future.